1997
DOI: 10.1051/jp4:19973126
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Twinning on the Constitutive Reponses of Zr : Experirnents and Modeling

Abstract: The stress-strain response of Zr due to twinning is distinctly different from that due to slip as a function of temperature and strain rate. When the applied stress is lower than the transition stress, dislocation slip is the dominant deformation mechanism. The traditional MTS model is shown to adequately represent the constitutive behavior of Zr. Above the transition stress twinning becomes the dominant deformation mechanism where the flow stress increases linearly with strain. In this regime the rate-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…An axisymmetric mesh with a total of 21,120 cells (165 TT cells, 8 radial cells and 16 azimuthal cells) was generated with the sample modeled as a two-material (specimen and ring) composite. The specimen material forms the 10 mm central plug pressed into an outer ring of material having potentially different elastoplastic properties due to textural and other microstructural differences (12). Stress wave reflection from the plug/ring interface due to property discontinuity could affect the wave profile results, but a radial transit time of 1.05 µs for the plug precludes any such effect during the HEL loading phase.…”
Section: Hugoniot Elastic Limit Analysismentioning
confidence: 99%
“…An axisymmetric mesh with a total of 21,120 cells (165 TT cells, 8 radial cells and 16 azimuthal cells) was generated with the sample modeled as a two-material (specimen and ring) composite. The specimen material forms the 10 mm central plug pressed into an outer ring of material having potentially different elastoplastic properties due to textural and other microstructural differences (12). Stress wave reflection from the plug/ring interface due to property discontinuity could affect the wave profile results, but a radial transit time of 1.05 µs for the plug precludes any such effect during the HEL loading phase.…”
Section: Hugoniot Elastic Limit Analysismentioning
confidence: 99%
“…It also is a critically important nuclear material in that the Zircaloy alloy (Zircaloy-2: Zr-1.5Sn-0.15Fe-0.1Cr-0.05Ni) is widely used as nuclear fuel cladding due to its combination of good corrosion resistance and low neutron absorption [11]. Table 10.11 lists several data sets that are considered here [12][13][14][15][16]. Pure zirconium has an HCP structure (alpha) at temperatures below 1143 K (T H = 0.538); above this temperature, a transformation to the BCC (beta) structure occurs.…”
Section: Pure Zirconiummentioning
confidence: 99%
“…Chen and Gray [15] reported full stress-strain curves in pure zirconium over a wide range of temperature and strain rates (see Table 10.11). Strain hardening-or structure evolution-is analyzed using Equation (9.7), with obstacles 1 and 2 instead of p and i in an identical manner as was demonstrated in pure magnesium (Figure 10.19).…”
Section: Structure Evolution In Zirconiummentioning
confidence: 99%
See 1 more Smart Citation
“…Material: Pure Zr Grain size ¼ 1 mm Driving forces from Thermo-Calc software, PURE database: 128, 234, 346, 433, 505, 568 and 629 J/mol at 300 K, 373 K, 473 K, 573 K, 673 K, 773 K and 873 K, respectively [42] Thermodynamic coefficients: A ¼ 2376 J/mol, B ¼ 7128 J/mol, C ¼ 4752 J/mol [14] Gradient coefficient (b) ¼ 1.06066 x 0 À11 J/m [14] Molar volume (V m ) ¼ 14 x 10 À6 m 3 /mol Interface thickness (d) ¼ 1 nm [14] Interfacial energy (g) ¼ 0.01 J/m 2 [14] Lattice constants: a a ¼ 3.232 Å, c a ¼ 5.147 Å, a u ¼ 5.039 Å, c u ¼ 3.136 Å [38,43]. Shear modulus (G) ¼ 36.3 GPa [44], Poisson ratio (n) ¼ 0.331 [44] Yield stresses: s a y ¼ 180 MPa, s u y ¼ 1180 MPa [45] Hardening modulus (H) ¼ 1300 MPa[46] Plastic relaxation rate (k)¼ 10 GPa À1 s À1 Interfacial kinetic coefficient (L) ¼ 1 m 3 J À1 s À1observed that the entire a grain transforms into an u grain when Zr is soaked for 24 h[2].Rabinkin et al have observed ellipsoidal u particles in Zr when soaked under pressure for 4 h, a morphology that can be observed during the b À u phase transformation in ZreNb alloys…”
mentioning
confidence: 99%